Success thrives where academic resilience is nurtured, and happiness is valued - Kaur, Paramjeet; Cheema, Guneet Kaur; Singh, Navneet (Journal of Interdisciplinary Studies in Education, 2026)
Teenagers often struggle to achieve academic excellence due to a lack of emotional regulation. Emotional factors significantly influence their academic and personal development during this period. This research looks to explore how academic resilience relates to happiness. The present study has focused on finding a correlation between academic resilience and happiness. This study has hypothesized both alternative and null hypotheses. The total number of samples constituted for the present study was 100 from various disciplines. Data were collected through a Google form on academic resilience 5-point Likert scale, and the Oxford Happiness Questionnaire. The collected data were analyzed using Pearson correlation, followed by regression analysis. The statistical results revealed a strong positive correlation between academic resilience and happiness, and the regression model revealed that academic resilience has strong predictive power for happiness.